Economic crises and the reform programs: Will the IMF assistance rescue Lebanon? - Ishker, Nermeen; Youssef, Jamile (International research journal of management, IT and social sciences, 2022)
Lebanon has been passing through considerable difficulties as a result of compounded economic and financial degradation. Therefore, a comprehensive adjustment program is necessary. The aim of this research is to describe different reform plans applied by countries that have undergone economic and financial crises. More particularly, it discusses nations that implemented the International Monetary Fund reform programs; the purpose, plan, requirements and policies of the program are also identified. Furthermore, this paper highlights the reasons behind the success or failure of a nation in implementing a development program to anticipate whether an agreement with the IMF will be the solution for the Lebanese case.